2020
DOI: 10.1016/j.adolescence.2019.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Relational aggression and victimization during adolescence: A meta‐analytic review of unique associations with popularity, peer acceptance, rejection, and friendship characteristics

Abstract: Introduction: This meta-analysis includes 46 studies including 35,468 adolescents (M age = 12.4 years) with a mean sample ages between 10 and 17 years. Just over half of the studies include samples drawn from the U.S. with the remaining samples representing 11 different countries. Method: We examined the magnitude of overlap between relational aggression and relational victimization and, using infrequently used semipartial correlations as effect sizes, we examined unique associations of each with peer acceptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 59 publications
11
60
0
Order By: Relevance
“…The rejected status is used to classify youths who receive a high number of least liked nominations and only a few liked most nominations (Farmer, Lines, & Hamm, 2011). Victims of bullying tend to have a lower status than their perpetrators, and they tend to be rejected and have lower levels of social competence (Casper, Card, & Barlow, 2020;Salmivalli et al, 1996). They also tend to be less popular, and to be overrepresented in the rejected status group (Boulton & Smith, 1994;Guy, Lee, & Wolke, 2019; for a recent meta-analysis on the association between victimization and social status, see; Casper et al, 2020).…”
Section: Peer Social Status and Bullying Involvementmentioning
confidence: 99%
“…The rejected status is used to classify youths who receive a high number of least liked nominations and only a few liked most nominations (Farmer, Lines, & Hamm, 2011). Victims of bullying tend to have a lower status than their perpetrators, and they tend to be rejected and have lower levels of social competence (Casper, Card, & Barlow, 2020;Salmivalli et al, 1996). They also tend to be less popular, and to be overrepresented in the rejected status group (Boulton & Smith, 1994;Guy, Lee, & Wolke, 2019; for a recent meta-analysis on the association between victimization and social status, see; Casper et al, 2020).…”
Section: Peer Social Status and Bullying Involvementmentioning
confidence: 99%
“…However, there was substantial variability around the effect size and moderation analyses suggested that the effect size decreased with developmental period (i.e., weaker in late adolescence than in childhood or early adolescence). Casper, Card, & Barlow, 2020 (this issue) examined the association between relational aggression and victimization, and the impact of several peer correlates. Using semi‐partial correlations (described above), Casper and colleagues found that relational aggression was associated with decreased peer acceptance, partially due to its association with victimization (i.e., adolescents who are not well liked tend to be aggressive and victimized); victimization was related to decreased peer acceptance, above and beyond relational aggression (i.e., victimized adolescents tend not to be well liked, regardless of aggression).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…As can be seen by the diverse approaches used in articles in this special issue, researchers have many options available for conducting meta‐analyses (e.g., multivariate meta‐analysis, network meta‐analysis, as discussed by Thompson & Semma, 2020) and open‐source, user‐friendly software is increasingly available. In addition, there are a variety of techniques to examine the associations between constructs across studies, such as meta‐regression (Vannucci, Simpson, Gagnon, & Ohannessian, 2020; White, Pasco, Korous, & Causadias, 2020) and semi‐partial correlations (Casper, Card, & Barlow, 2020). This special issue showcases some of the various tools available to adolescent researchers conducting meta‐analyses.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations